To both/and, either/or, in-between, and beyond! Queering the normative construction of entrepreneurship for the inclusion of queer entrepreneurs. - Rees, Rhiannon J (Graduate School of Business (GSB), 2023)
The alleged universality of entrepreneurship as a neutral, meritocratic, and accessible means through which individuals are free to realise their socioeconomic potential has been challenged. The entrepreneurship literature is dominated by a narrow stereotype of the entrepreneur (white, neoliberal, Western, male, heteronormative) but the interest in entrepreneurship as a mechanism for economic and social value creation is driving demand for more inclusive, diverse, and pluralist knowledge on entrepreneurship that is representative of marginalised populations' lived experiences. Many have already introduced alternative constructions of entrepreneurship; however, the literature on LGBT and queer entrepreneurs is still limited. This paper aims to help address this gap by queering entrepreneurship through a ‘de- and re-construction' of the norm. Drawing from both post-structural feminism and queer theory, this study problematises ‘normativity' both in entrepreneurship and in the methodologies used to study it. This study asked seven self-identified queer entrepreneurs in South Africa to develop and explain a queer-inclusive construction of entrepreneurship through collage. Collages were analysed through a visual grounded theory methodology and supplemented with interview data analysed through a constructivist grounded theory methodology. The findings confirm the pervasiveness of a normative construction of entrepreneurship and indicate the need to queer it by both including queer individuals and destabilising normative identities and methodologies in the entrepreneurship field. This study contributes to a more inclusive, diverse, and representative entrepreneurial discourse by illuminating specifically the lived experience of queer African entrepreneurs, highlighting the pressure they face to conform to both a Western stereotype of the entrepreneur and to being the ‘right' kind of queer as a product of queernormativity. This research also illustrates how fresh ontologies can inject the entrepreneurship literature with new perspectives that challenge normative, positivist hierarchies. Recommendations for practical interventions for inclusivity are discussed and future directions for research are suggested.